THE SIGNIFICANCE OF MATRIX METALLOPROTEINASES IN THE DEVELOPMENT OF PERIODONTITIS (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
In recent decades, there has been a growing interest in non-invasive diagnostic methods. Saliva is one of the safe biomaterials for studying the human body. The correlational increase in salivary composition and it’s metabolic products, particularly the product of connective tissue degradation and metalloproteases gives the possibility of its widespread use in diagnosis.